The cost and cost-effectiveness of a text-messaging based intervention to support management of hypertension in South Africa - Hongoro, Danleen James (Health Economics Unit, 2018)
This project assessed the cost and cost-effectiveness of hypertension management in South Africa within the context of a text messaging-based intervention (StAR* study) conducted in an urban public-sector clinic in Cape Town. The StAR* study is a community randomized trial that investigated the effect of adherence support via short messaging service (SMS) on treatment adherence and patient outcomes for the management of hypertension at Vanguard CHC in Cape Town (Bobrow et al. 2016). Patients received behavioral text messages as reminders for them to collect and take their medication on time. The StAR* study, consisted of three arms that ran in parallel: participants in the control arm received unrelated messages; patients in the information-only arm received one-way information messages twice a week; and patients in the interactive arm received interactive SMS-texts at the same frequency as those in the information only arm (Bobrow et al. 2016). Patients in the interactive arm could respond to the messages and trigger a response from the healthcare provider. The text messaging based intervention was shown to improve hypertension outcomes over a 12-month period in hypertension patients by improving adherence and retention in care. The study showed, in the one-way intervention arm an improvement in adherence (measured by medication refill rates) and a small reduction in systolic blood pressure (2.2mm Hg reduction over 12months) (Bobrow et al. 2016). In this study, we assessed the cost and cost effectiveness of the StAR* intervention under routine care management at Vanguard CHC. We also assessed the cost of hypertension management from the health system perspective and the cost of accessing hypertension care from the patient perspective. A combination of the ingredients approach and step-down costing was used to cost hypertension care from a health system perspective while a questionnaire was administered to 250 patients to estimate patient costs. The primary outcomes were the average cost of hypertension care and the incremental cost of the text message-based adherence intervention (StAR* intervention), compared to usual care, per millimetre of mercury (mmHg) reduction in systolic blood pressure. Results of the study show that the average health system cost for hypertension management is R262 per visit and the patient cost of accessing hypertension care is R172 per visit. The text messaging based intervention was found to have low implementation costs in this pilot phase. The monthly incremental cost of the text messaging based intervention cost was R4 per person. The incremental cost-effectiveness ratio of the intervention was R22 per mm Hg reduction. This study provides the first contemporary assessment of hypertension management costs and the cost-effectiveness of mobile-based hypertension adherence support in South Africa. Future work will seek to estimate the long-term cost-effectiveness of this intervention and the cost of scaling it to the provincial and national levels.